PENGEMBANGAN SISTEM INFORMASI PELATIHAN BERBASIS WEB MENGGUNAKAN TEKNOLOGI WEB SERVICE DAN FRAMEWORK LARAVEL - Ramos Somya; Tan Michelle Esmeralda Nathanael (Jurnal Techno Nusa Mandiri, 2019)
Pincher ID is a local startup that engaged in the education sector especially for providing training classes. For now, Pincher ID based on a mobile application that causes only a third party (Google Play store/ App Store) who can access it. Furthermore, mobile application Pincher ID is not indexed by search engine so it makes difficult for people to find it. In this research, training information system web-based with web service technology and framework Laravel will be built. Web service technology applied to the system for data integration so data can be stored centrally. The architecture of web service used in the system is REST because accessing REST with URL address on browser application, give easy access to the application. In this research, prototype method used to develop an information system based on a website that can be used by Pincher ID. The test result showed that the training information system worked well and in accordance with the user’s wishes.